Inheritance Rights of Children Born Out of Wedlock: Analysis from the Perspective of Shafi'i School of Jurisprudence and the Civil Law Code (Children of Zina) with an Educational Approach - Ulwi, Nurkholis; Masnun, Masnun; Zuhdi, Muhammad Harfin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study delves into the inheritance rights of children born out of wedlock, particularly focusing on the perspective of the Shafi'i School of Jurisprudence and the Civil Law Code concerning children born out of Zina, while employing an educational approach. The aim is to provide insights into the complexities surrounding inheritance rights in such cases and to propose educational strategies for addressing related issues. A qualitative research approach is adopted, utilizing a combination of literature review and legal analysis. Data is collected through in-depth examination of legal texts, scholarly articles, and case studies related to inheritance rights of children born out of wedlock in Islamic law and civil law. Data is collected through extensive review of relevant legal sources and literature, focusing on the interpretation of inheritance laws and principles within the Shafi'i School of Jurisprudence and the Civil Law Code. The analysis involves identifying key themes, patterns, and discrepancies in the treatment of inheritance rights for children born out of wedlock. The findings reveal varying interpretations and legal provisions regarding inheritance rights for children born out of wedlock within Islamic law and civil law. While Islamic law recognizes inheritance rights for such children, civil law may impose restrictions based on legal requirements and societal norms. The implications of this study highlight the need for educational interventions aimed at raising awareness and promoting understanding of inheritance rights among stakeholders, including religious leaders, legal practitioners, and the general public. By fostering dialogue and collaboration, educational initiatives can contribute to the development of more equitable and inclusive legal frameworks.